2020
DOI: 10.1155/2020/3232869
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exosomal microRNAs and Oxidative Stress in Neurodegenerative Diseases

Abstract: Neurodegenerative diseases including Alzheimer’s disease and Parkinson’s disease are aging-associated diseases with irreversible damage of brain tissue. Oxidative stress is commonly detected in neurodegenerative diseases and related to neuronal injury and pathological progress. Exosome, one of the extracellular vesicles, is demonstrated to carry microRNAs (miRNAs) and build up a cell-cell communication in neurons. Recent research has found that exosomal miRNAs regulate the activity of multiple physiological pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 167 publications
(146 reference statements)
0
76
0
Order By: Relevance
“…Although the origin of AD remains unknown, several experimental studies indicate that exosomes distribute neurotoxic molecules between neuronal cells, playing a crucially important role in AD progression [ 22 ]. MSC-Exos may use the same pathways (gap junctions, synaptic transmission, endosomal/lysosomal secretion system) to deliver MSC-sourced neuroprotective and trophic factors in injured neurons, preventing AD progression [ 5 , 12 ].…”
Section: Therapeutic Effects Of Msc-exos In the Treatment Of Alzhementioning
confidence: 99%
“…Although the origin of AD remains unknown, several experimental studies indicate that exosomes distribute neurotoxic molecules between neuronal cells, playing a crucially important role in AD progression [ 22 ]. MSC-Exos may use the same pathways (gap junctions, synaptic transmission, endosomal/lysosomal secretion system) to deliver MSC-sourced neuroprotective and trophic factors in injured neurons, preventing AD progression [ 5 , 12 ].…”
Section: Therapeutic Effects Of Msc-exos In the Treatment Of Alzhementioning
confidence: 99%
“…It has been proposed that miRNAs are helpful in this regard [16]. In the previous few years, collective exploration has shown the significant jobs of miRNAs in the advancement of BC [17].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-96 has been accounted for to apply an oncogenic impact in non-little cell cellular breakdown in the lungs, esophageal malignancy, hepatocellular carcinoma, bosom disease [5]. The objective qualities of miR-96 incorporate the tumor silencer qualities FOXO1 and FOXO3a in bosom malignancy [19] and other approved focuses of miR-96 remember RECK for esophageal disease [18], EphrinA5 in Hepatocellular carcinoma [19], SAMD9 in non-little cell cellular breakdown in the lungs (NSCLC) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown an increase in oxidative stress (OS) in the emergence of PD [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. PD is characterized by mitochondrial dysregulation as evidenced by increased production and subsequent release of reactive oxygen species (ROS) [ 30 ].…”
Section: Parkinson’s Disease and Oxidative Stressmentioning
confidence: 99%